2013
DOI: 10.1111/gcb.12228
|View full text |Cite
|
Sign up to set email alerts
|

Projecting demographic responses to climate change: adult and juvenile survival respond differently to direct and indirect effects of weather in a passerine population

Abstract: Few studies have quantitatively projected changes in demography in response to climate change, yet doing so can provide important insights into the processes that may lead to population declines and changes in species distributions. Using a long-term mark-recapture data set, we examined the influence of multiple direct and indirect effects of weather on adult and juvenile survival for a population of Song Sparrows (Melospiza melodia) in California. We found evidence for a positive, direct effect of winter temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 65 publications
3
70
0
Order By: Relevance
“…Although successional changes in plant structure and composition are due to the lack of human disturbance and suppression of natural disturbances (e.g., fire) since the early 1960s, our results support the conclusions of other studies that the indirect impact of climate change on bird abundance through changes in plant communities that provide bird habitat will be an important predictor of future climate-change impacts (Seoane et al 2004 and Inouye 2012). While rainfall did not explain a large percentage of the variance in densities, our results support previous work that show that annual weather rainfall patterns can contribute to vital rates (Chase et al 2005, Dybala et al 2013 and ultimately density (Silkey et al 1999, Dennis andOtten 2000).…”
Section: The Retrospective Applicationsupporting
confidence: 88%
“…Although successional changes in plant structure and composition are due to the lack of human disturbance and suppression of natural disturbances (e.g., fire) since the early 1960s, our results support the conclusions of other studies that the indirect impact of climate change on bird abundance through changes in plant communities that provide bird habitat will be an important predictor of future climate-change impacts (Seoane et al 2004 and Inouye 2012). While rainfall did not explain a large percentage of the variance in densities, our results support previous work that show that annual weather rainfall patterns can contribute to vital rates (Chase et al 2005, Dybala et al 2013 and ultimately density (Silkey et al 1999, Dennis andOtten 2000).…”
Section: The Retrospective Applicationsupporting
confidence: 88%
“…The findings of this study (1) showed that the reproductive morphology of the smooth‐billed ani was similar to that observed in other birds such as domestic quail, fowl, emu, ostrich, goose, parakeet and drake (Aire, 2002; Aire & Soley, 2000; Leska, Kiezun, Kaminska, & Dusza, 2015; Parizzi et al, 2008; Peixoto et al, ; Reed, Cope, & Blackford, 2011); (2) indicated intense gonadal activity throughout the wet season that was consistently similar to what is described in other birds during the breeding season (Baraldi‐Artoni et al, ; Kim & Yang, ; Leska & Dusza, ; Peixoto et al, ; Tae et al, ); (3) and revealed remarkable signs of gonadal involution and low gametogenic activity after precipitation decreased. Birds inhabiting areas with adverse climate characteristics exhibit flexibility with regard to the timing and intensification of breeding activity whenever environmental conditions are satisfactory to ensure reproductive success and offspring survival (Cruz‐McDonnell & Wolf, ; Dybala, Eadie, Gardali, Seavy, & Herzog, ; Quintero, González‐Caro, Zalamea, & Cadena, ; Sandoval, ; Selwood et al, ). Increased precipitation rates usually determine high food and water availability in drought areas (Langin et al, ); therefore, opportunistic breeding usually follows intense single‐event rainfall and lasts until precipitation rates decline dramatically (Hahn et al, ; Mares, Doutrelant, Paquet, Spottiswoode, & Covas, ).…”
Section: Discussionmentioning
confidence: 99%
“…If mismatches with timing of peak resource abundance increase with warming, it may be less effective to raise a second brood [81]. Other fitness components, such as nest success of individual pairs and adult survival (e.g., [82]) may be impacted by phenological shifts. Consequently, we hesitate to say that shifts in timing will not have fitness impacts in the species we studied.…”
Section: Discussionmentioning
confidence: 99%